2020
DOI: 10.14302/issn.2690-4837.ijip-18-2238
|View full text |Cite
|
Sign up to set email alerts
|

Perspective for Methicillin-resistant Staphylococcus Aureus colonization, Antibiotic Susceptibility Patterns and Risk factors for Colonization among People Living with HIV at Nyenga Hospital, Buikwe District, in Central Uganda

Abstract: Background Colonization with methicillin-resistant Staphylococcus aureus (MRSA) is recognized as an association towards development of infections that may cause of morbidity among people living with Human Immunodeficiency Virus (PLWHIV). We report on the prevalence, antibiotic susceptibility pattern and risk factors associated with MRSA carriage among PLWHIV at Nyenga hospital, Buikwe district in central Uganda. Materials and Methods We conducted a cross-sectional study among PLWHIV attending Nyenga hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 28 publications
(24 reference statements)
1
3
1
Order By: Relevance
“…In the present study the whole isolates of S. aureus including MRSA showed full resistance for Penicillin which is in agreement with a study conducted in Uganda [18]. Like the present study another study [8] also indicated all MRSA isolate were found to be resistance to cefoxitin and penicillin.…”
Section: Plos Global Public Healthsupporting
confidence: 92%
See 4 more Smart Citations
“…In the present study the whole isolates of S. aureus including MRSA showed full resistance for Penicillin which is in agreement with a study conducted in Uganda [18]. Like the present study another study [8] also indicated all MRSA isolate were found to be resistance to cefoxitin and penicillin.…”
Section: Plos Global Public Healthsupporting
confidence: 92%
“…with a study conducted in Ethiopia among pediatric HIV patients [2] but another study in Ethiopia reported a lower prevalence of S. aureus colonization among adult HIV patients (39.7%) [6]. Still, a very low rate was also reported in another similar studies in Ethiopia, other African countries and China [10,17,18,27]. In contrary to the present study almost two fold higher MRSA colonization was reported in a study conducted in East Africa [28].…”
Section: Plos Global Public Healthcontrasting
confidence: 90%
See 3 more Smart Citations